Scope of Practice and Principles of Care of Naturopathic Medicine in North America: A Commentary - Leslie Solomonian (MDPI AG, 2021)
Naturopathic medicine is a growing profession in North America that provides expertise in complementary and alternative, or integrative care to pediatric patients. It is imperative that healthcare providers have an understanding of the training and scope of other health professionals in order to effectively make decisions regarding research, collaborative clinical care, and policy. Given the prevalence of use of complementary and alternative medicine by children and families in North America, and the growing interest in "integrative" medicine, we aim to offer an overview of naturopathic care for children. This document describes the principles, training, and scope of naturopathic medicine, including health promotion, disease prevention, and illness management. It describes the process by which naturopathic doctors create an integrative healthcare plan for children, evaluate and apply evidence, and integrate ethical issues in practice management, and speaks to the role naturopathic doctors have regarding advocacy for community and planetary health as it relates to pediatrics.